Relationship between home garden ownership and the consumption of fruits and vegetables - Mahama Saaka; Simon Awini; Fred Kizito; Eric Nang (Cambridge University Press, 2024)
Abstract Objective: This study assessed the extent to which access to home gardens associate with the frequency of fruit and vegetable (FV) consumption. Setting: The study was carried out in fifty rural communities in Northern Ghana where food insecurity and malnutrition including micronutrient deficiencies are prevalent. Design: A community-based comparative analytical cross-sectional study. Participants: A sample of 847 randomly selected rural households. Results: The proportion of households that consumed FV at least 3 d in a week was 45 %. Members in households who owned a home garden were 1·5 times more likely to consume FV at least 3 d in a week (adjusted OR (AOR) = 1·46 (95 % CI 1·06-2·0)), compared with their counterparts who had no home gardens. Furthermore, households in which mothers had a positive attitude towards FV consumption were 1·6 times more likely to consume FV (AOR = 1·63 (95 % CI 1·17-2·27)) compared with mothers who were less positive. Conclusions: Our results suggest that food and nutrition policy measures that promote home gardens can improve consumption of diversified diets including FV among vulnerable rural households in Northern Ghana. Additionally, households with lower income may benefit from nutrition behaviour change communication campaigns directed towards increasing a positive attitude to FV intake.